Characterization of high efficiency solar cells - Chan, Zhi Hao. (2011)
Solar cells are a promising renewable energy, carbon- free electric energy resource to address the fossil fuel shortage and global warming issues. This report reviews the characterization of high efficiency solar cells through experiment by using different types of solar cell; single-junction solar cells and multi-junction solar cells. The report begins with a brief history of solar cells, then the report with be mentioning about the basic principle and theory of semiconductor which will explain how solar cells work. Moving on, the report will state a few parameters that are important when fabricating solar cell or manufacturing them which will affect their efficiency. An experiment was done to test the efficiency of solar cells on different types of cells and materials. For the experiment, under single-junction cell, it will have solar cells using different semiconductor material like Germanium (Ge) and Gallium Arsenide (GaAs). This is to find out whether different bandgap will affect the efficiency of solar cell. Under multi-junction cells, the experiment will carry out only dual-junction cell which is Gallium Indium Phosphide (GaInP) and Indium Gallium Arsenide (InGaAs). This is to find out whether will which of these two materials will be the limiting factor for the responsivity. The results of this experiment concluded that the lower the bandgap, the lower the efficiency of the solar cells. In addition, the difference in lattice structure also affects the efficiency of the cells as well. The limitation of this experiment is that it was not done under the actual sunlight; therefore the equipment used could be stronger or weaker than the sunlight.